Are explorers greener? Investigating the role of personality traits, connectedness to nature and attitudes toward exploring in various pro-environmental behaviors - Veronica Muffato; Laura Miola; Francesca Pazzaglia; Francesca Pazzaglia; Chiara Meneghetti; Chiara Meneghetti (Frontiers in Psychology)
Previous research has suggested that individual characteristics, such as personality traits, are crucial for pro-environmental behaviors. However, the joint role of more specific environment-related individual dispositions on various pro-environmental behaviors has not yet been investigated and is the aim of this study. A total of 649 adults (18–59 years old) assessed their pro-environmental behaviors, personality traits, the connectedness to nature, attitudes toward exploration, and spatial anxiety. Personality traits (openness and conscientiousness) were related to some of the pro-environment behaviors (transportations and purchasing). Connectedness to nature was the factor most associated with the pro-environment behaviors (conservation, citizenship, purchasing). Moreover, newly we showed that attitudes toward exploration were associated with citizenship and purchasing behaviors. Overall, the results newly highlighted the importance of environment-related characteristics alongside general personality traits. Fostering environmental-related personality factors, such as connection to nature and attitudes towards exploration, may drive positive environmental action, suggesting novel approaches to build a more sustainable society.